Herbert Grundmann (1902-1970) : essays on heresy, inquisition, and literacy - Grundmann, Herbert, 1902-1970 (Heresy and Inquisition in the Middle Ages Ser., 2019)
In the field of medieval religious history, few scholars have matched the originality of the German academic Herbert Grundmann (1902-1970). Trained at the University of Leipzig and president of the Monumenta Germaniae Historica from 1959 until his death, Grundmann published a series of brilliant books and articles that fundamentally reshaped how historians of culture and religion conceptualized the medieval past. Yet although later generations of scholars have since approached their research from vantage points shaped by his arguments, few of his writings have been previously accessible to an Anglophone audience. This volume presents translations of six of Grundmann's most significant essays on the intertwined themes of medieval heresy, literacy, and inquisition. Together, they offer new access to Grundmann's scholarship, one which will catalyze new perspectives on the medieval religious past and enable a fresh consideration of his intellectual legacy in the twenty-first century. JENNIFER KOLPACOFF DEANE is Professor of History at the University of Minnesota, Morris